IMPLEMENTATION OF VISIBLE LIGHT COMMUNICATION BASED SYSTEM FOR INDOOR POSITIONING - Nasar, Abdul Wahab; Sohail, Muhammad; Ali Bokhari, Syed Muzamil; Kasi, Jafar Kha; Kasi, Ajab Khan (MATTER: International Journal of Science and Technology, 2017)
Visible light communication (VLC), have gain much interest in past decade in indoor communication. In particular, it is use for illumination and communication simultaneously. White light emitting diodes which are used as a transmitter for VLC are potential candidates for localization. Conventionally global positioning system (GPS) has very poor performance in indoor environments. Assisted global positioning system (AGPS) has positioning accuracy in few meter range. WLEDs can be used in small cell area inside the room hence indoor positioning can be measured accurately in centimeter. In this paper a WLEDs based indoor position system is investigated, the position was accurately confined in 11cm with low cost and on the shelf components.